2012
DOI: 10.3844/ajbbsp.2012.220.229
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compounds Removal Methods: A Review

Abstract: Volatile Organic Compounds (VOCs) are among the most toxic chemicals which are detrimental to humans and environment. There is a significant need of fully satisfactory method for removal of VOCs. There are several methods including physical, chemical and biological treatments available to remove VOCs by either recovery or destruction. The aim of the present study is to summarize the available methods for VOC removal; trying to find a promising method among the available techniques. A wide range of VOCs can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(35 citation statements)
references
References 39 publications
0
31
0
4
Order By: Relevance
“…They can cause drowsiness, headache, dizziness and cancer for long-term inhalation or exposure [24][25][26][27]. Consequently, a colloidal crystal-based colorimetric chemical sensor was developed by Endo et al to specifically determine VOC concentrations [28].…”
Section: Sensing Of Volatile Organic Compoundsmentioning
confidence: 99%
“…They can cause drowsiness, headache, dizziness and cancer for long-term inhalation or exposure [24][25][26][27]. Consequently, a colloidal crystal-based colorimetric chemical sensor was developed by Endo et al to specifically determine VOC concentrations [28].…”
Section: Sensing Of Volatile Organic Compoundsmentioning
confidence: 99%
“…Recent epidemiological studies (Rappaport and Kupper 2004;Alvarez-Hornos et al 2008;Berenjian, Chan, and Malmiri 2012;Huang et al 2014) have shown the serious effects of environmental pollution on human health. The accumulation of volatile organic compounds in the atmosphere remains one of the main causes of some diseases, including cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohols, including ethanol, n-propanol, isopropanol and n-butanol, are the common compounds as VOCs. Ethanol is an important raw material in chemical industry, but long-term exposure to ethanol vapors leads to nausea, headache, dizziness and cancer [2][3][4]. Isopropanol is widely used in the manufacture of paints and printing, but the emission of isopropanol can be photochemical oxidants which cause "summer smog" and destroy the body's respiratory system and eyes.…”
Section: Introductionmentioning
confidence: 99%